PENGARUH KADAR PROSTATE SPECIFIC ANTIGEN (PSA) DAN KADAR KALSIUM TERHADAP GLEASON SCORE PADA PASIEN ADENOKARSINOMA PROSTAT DI RSPAD GATOT SOEBROTO TAHUN 2019-2022 - Melinda Novy Ramadhani (2023)
Prostate adenocarcinoma is the most common malignancy occurring in the prostate, accounting for approximately 95%, and ranks fifth as the most common cancer in men. Calcium is known to be one of the risk factors influencing the development of prostate adenocarcinoma. The examination of PSA levels is an important serum marker for diagnosing prostate adenocarcinoma, while the degree of differentiation can be assessed using the Gleason score system, which serves as a good prognostic predictor. This study aims to determine the influence of PSA levels and calcium levels on Gleason scores in patients with prostate adenocarcinoma at RSPAD Gatot Soebroto from 2019 to 2022. The research method employed is an analytical observational study with a cross-sectional research design using medical record data from 60 patients with prostate adenocarcinoma. The research analysis utilizes the Spearman correlation test. Bivariate analysis results indicate no significant relationship between calcium levels and Gleason scores with a p-value of 0.559, while a significant relationship is observed between PSA levels and Gleason scores with a p-value of 0.002. The conclusion drawn is that there is a significant correlation between the influence of PSA levels and the Gleason score in patients with adenocarcinoma of the prostate, and there is no significant correlation between the influence of calcium levels and the Gleason score in patients with adenocarcinoma of the prostate at RSPAD Gatot Soebroto from 2019 to 2022.